ELECTRONIC SPECTRAL CHARACTERIZATION AND ANTIBACTERIAL ACTIVITY OF LANTHANIDE (III) - CEFTAZIDIME COMPLEXES - Singhal, Preeti; Jain, Renuka; Goyal, Deepti (International Journal of Engineering Technologies and Management Research, 2018)
The present work describes the spectrochemical study of some Lanthanide (III) - ceftazidime (Ln(III)-CEFZ) complexes. The impact of the ligand environment on electronic spectrum of the lantanide ion with special reference to complexation and nature of Ln-ligand bond has been examined. The energy and intensity parameters for the complexes have also been evaluated. The ligand and all prepared complexes were screened for their antibacterial activities against Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus and the results showed that antibacterial activity of ligand on complexation have been enhanced.